Perspektif HAM Dan Maqashid Syari’ah Dalam Meninjau Kebijakan Hukuman Mati Dalam Undang Undang No. 1 Tahun 2023 Tentang KUHP - Anggraini, Rooza Meilia; Maksum, Muh.; Dewi, Arlinta Prasetian (Institut Agama Islam Negeri Ponorogo, 2024)
The death penalty is a form of punishment whose existence is a topic of debate. Death penalty regulations in Indonesia experienced dynamics, until the enactment of Law Number 1 of 2023 concerning the Criminal Code. In this latest law, the death penalty sanction can be changed to life imprisonment if the convict shows good behavior for 10 years. The aim of this research is to understand how the principles of human rights and maqashid sharia are applied in the death penalty policy regulated in Law no. 1 of 2023. This research is included in literature research with a legislative approach to question the existence of the latest regulations regarding the death penalty, whether they are in line with or contrary to human rights principles and maqashid sharia. The research results show that the change in the status of the death penalty is not in line with human rights. This happens because humans basically have the same rights to own their lives. The right to life must not be taken away by anyone, so those who have taken the lives of others without justifiable reasons, at the same time have ignored other universally respected human rights. Meanwhile, if viewed from the perspective of maqashid sharia, changes in provisions regarding the death penalty are not relevant to the objectives of sharia in terms of preserving the soul (hifdz an nafs), where there is no guarantee that the convict will not repeat the same act in the future. The results of this research should be able to evaluate the social impact and how the policy affects society and the legal system in Indonesia.